2002
DOI: 10.1080/1355621021000005973
|View full text |Cite
|
Sign up to set email alerts
|

Intravenous flumazenil versus oxazepam tapering in the treatment of benzodiazepine withdrawal: a randomized, placebo‐controlled study

Abstract: Flumazenil (FLU), a benzodiazepine (BZD) partial agonist with a weak intrinsic activity, was previously found unable to precipitate withdrawal in tolerant subjects submitted to long-lasting BZD treatment. The potential use of FLU to treat BZD withdrawal symptoms has also been evaluated tentatively in clinical studies. In the present experiment, FLU (treatment A) was compared with oxazepam tapering (treatment B) and placebo (treatment C) in the control of BZD withdrawal symptoms in three groups of BZD dependent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
65
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(67 citation statements)
references
References 34 publications
2
65
0
Order By: Relevance
“…Pregabalin has demonstrated to be effective in the treatment of BD and BWS, exerting its beneficial action by reducing the severity of withdrawal and anxiety symptoms. [19,20]; β-blocker propranolol [21,22]; α2-agonist clonidine [23]; 5-HT 1A partial agonist buspirone [19,20,24]; anxiolytic alpidem [25]; neuroactive steroid progesterone [26]; 5-HT 3 antagonist odansetrone [27]; and BZD partial agonist flumazenil [28,29].…”
Section: Resultsmentioning
confidence: 99%
“…Pregabalin has demonstrated to be effective in the treatment of BD and BWS, exerting its beneficial action by reducing the severity of withdrawal and anxiety symptoms. [19,20]; β-blocker propranolol [21,22]; α2-agonist clonidine [23]; 5-HT 1A partial agonist buspirone [19,20,24]; anxiolytic alpidem [25]; neuroactive steroid progesterone [26]; 5-HT 3 antagonist odansetrone [27]; and BZD partial agonist flumazenil [28,29].…”
Section: Resultsmentioning
confidence: 99%
“…Although this phenomenon has been tested in BZ-dependent patients with inconsistent efficacy for counteracting tolerance in acute settings (Cittadini and Lader, 1991;Savic et al, 1991;Lader and Morton, 1992), a small clinical study has reported preliminary results on prolonged subcutaneous flumazenil administration in withdrawing BZ-dependent patients (Hulse et al, 2013), suggesting that perhaps longer treatments are needed in human populations. Another study using twice daily intravenous injections of flumazenil showed that flumazenil significantly blocked withdrawal symptoms and kept the patients better in abstinence (Gerra et al, 2002). Because flumazenil increases membrane targeting of GABA A receptors (Flaishon et al, 2003;Pericic et al, 2004), its efficacy in reversing BZ tolerance and in alleviating withdrawal in dependent subjects may at least partly be based on increased number of functional GABA A receptors.…”
Section: Effects Of Flumazenil On Benzodiazepine and Alcoholmentioning
confidence: 99%
“…In the United States and elsewhere, rapid detoxification in specialist clinics is fashionable, but for benzodiazepine users is potentially harrowing and dangerous (Gerra et al, 2002). Part of the ethos of Internet and face-to-face support groups is to offer continuous and extended support during what might be a year or more of tapering off benzodiazepines (Ashton, 2002;Kellagher, 2006;Samet, 2013).…”
Section: Support During Withdrawalmentioning
confidence: 99%
“…"Cold turkey" or rapid withdrawal can lead to fevers, acute psychotic states, seizures and even death (Ashton, 2005;Hu, 2011). Rapid detoxification in medical settings is rarely recommended and often requires the use of adjunct medication (Gerra et al, 2002). Most users are encouraged to undertake a steady taper in their own homes (Ashton, 2005) over a period of weeks, months or years, depending on dose and length of use (Ashton, 2002;Bristol and District Tranquilliser Project, 2013).…”
Section: Literature Reviewmentioning
confidence: 99%